ANALISIS PERAN MAHKAMAH KONSTITUSI DALAM PERLINDUNGAN HAM: TINJAUAN DARI PERSPEKTIF HUKUM TATA NEGARA - Nurhayati, Nurhayati; Salamah, Nadiyah; Marsela, Marsela; Khaerani, Naela Faiza; Maydikta, Rizka (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2025)
As a constitutional judicial institution, the Constitutional Court has the main function and task of reviewing laws against the 1945 Constitution, to ensure that current policies do not violate citizens' rights such as freedom of expression, educational rights and individual rights. The Constitutional Court has the authority to cancel laws that violate the constitution through a judicial review mechanism (Ashfiya et al., 2024). The articles on human rights in the 1945 Constitution show that Indonesia is a legal state that is committed to recognizing and respecting human rights. The 1945 Constitution also gives the Constitutional Court the authority to conduct judicial review in order to protect and guarantee human rights. The Constitutional Court not only has the authority as an institution to guard the constitution, but also has the authority to examine laws (Saldi Isra, 2024)